Strategy for Using Flyers on Social Media as a Means to Attract Public Reading Interest - Solikah, Alfiatu (Academia Publication, 2023)
The purpose of this study was to describe the activities of religious counselors and assess public interest in flyer media for guidance and counseling. Religious counselors were responsible for providing counseling services, developing guidance materials, and engaging in professional development. Before conducting counseling sessions, they had to prepare monographs, activity plans, guidance materials, and evaluation instruments. This qualitative study conducted observation, interviews, and documentary analysis as data collection techniques using a descriptive method. The findings indicated that religious counselors’ responsibilities included preparation, counseling services, work plan development, guidance material preparation, implementation, counseling assistance, religious conflict mediation, monitoring and evaluation, cross-sector collaboration, guidance model development, and the formulation of counseling guidelines. Additionally, flyer media effectively attracted public and congregants’ interest in reading, particularly when distributed as e-flyers through social media. E-flyers enabled faster, broader, and more targeted dissemination while incorporating a call to action that encouraged readers to explore further content on the religious counselor’s blog.